Development of Flipped Guided Inquiry Learning (FGIL) System Using Discord Application on Chemical Equilibrium - Ananda, Restu; Mawardi, Mawardi; Suryani, Okta (Jurnal Paedagogy, 2023)
This study aims to develop and analyze the validity and practicality of the Flipped Guided Inquiry Learning (FGIL) system using Discord application on chemical equilibrium. The research method used was Educational Design Research (EDR) with the Plomp model. Chemistry lecturers and teachers were experts and 12 students of grade XI SMAN 8 Padang who became subjects in this development research. The instruments used were the validity sheet for content validity and construct validity tests which were then processed using Aiken's V formula. In contrast, the practicality test's teacher and student response surveys included a practicality percentage. Based on the analysis results, it was found that the V values for content and construct validity were 0.88; and 0.89, with a valid category. Practicality results showed a value of 92% for students and 93% for teachers with a practical category. Therefore, the learning system created is reliable and useful for teaching.